Rodent models of immunologically induced-depression and anxiety related behaviour and associated biomarkers - McGuinness, Barry (Trinity College (Dublin, Ireland). Department of Physiology, 2014)
A series of rodent animal models of immune activation were assessed to develop an understanding of interactions between the immune system and brain leading to changes in behaviour and the determination of biomarkers of relevance to depression symptoms and its underlying pathophysiology.
Keywords: Neuroscience, Ph.D.; Ph.D. Trinity College Dublin